Umur, Jenis kelamin, durasi dila - Hesti Prawita Widiastuti; Frana Andrianur; arifin hidayat; Dedy Setiawan (Husada Mahakam, 2022)
One of the most dangerous diseases in the world is cardiovascular disease. Cardiac arrest is one of the major causes of death in the heart. Cardiopulmonary Resuscitation (CPR) is the first help that can be given. The aim of the research is to determine out the factors influence CPR success. An analytical observational research design with a cross sectional method used in this study. All patients who suffered cardiac arrest and completed CPR in the emergency department were included in this study, with a total of 42 participants. The age component accounted for 66.7 percent of the 60-year-olds, with male sex accounting for 61.9 percent. Prearrest diagnostic was Non-cardiac at 64.3 percent, Initial was Unshockable (asystole/PEA) at 71.4 percent, and the greatest duration of CPR was 1 minute by 81 percent. The chi square and fisher's exact tests revealed that there was no correlation between age (0.578), gender (1,000), and CPR duration (0.151) and CPR success. At Abdul Wahab Sjahranie Hospital Samarinda, there is a correlation between pre-arrest diagnosis (0.003), initial cardiac rhythm (0.041), and reaction time (0.013) and CPR success. Factors related to the success of CPR are pre-arrest diagnosis (0.003), initial heart rhythm (0.041), and response time (0.013).